1977
DOI: 10.3109/00498257709036242
|View full text |Cite
|
Sign up to set email alerts
|

Drug Metabolism under Pathological and Abnormal Physiological States in Animals and Man

Abstract: The activity of microsomal drug-metabolizing enzymes is altered by several pathological or abnormal physiological states, such as changes in nutritional status, liver, heart or kidney diseases, hormonal disturbances, pregnancy, tumour-bearing state, adjuvant arthritis, changes in reticuloendothelial system and environmental factors (stress, irradiation, heavy metals). The activities of other metabolic pathways, such as glucuronidation, sulphate conjugation, acetylation and alcohol oxidation are generally affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

1978
1978
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(49 citation statements)
references
References 312 publications
1
47
0
1
Order By: Relevance
“…In the dog, Vesell et al (1973) found a good inverse correlation between antipyrine T, and the activity of hepatic microsomal aniline hydroxylase and ethylmorphine N-demethylase whereas in man Davies, Thorgeirsson, Breckenridge & Orme (1973) were unable to demonstrate a correlation between antipyrine clearance and the rate of N-demethylation of the ethylmorphine in vitro. Furthermore, in vivo and in vitro studies in laboratory animals suggest that thyroid hormone may inhibit the N-demethylation of aminopyrine (Kato & Gillette, 1965;Kato, 1977). Brunk et al (1974) found no change in dipyrone metabolism when liothyronine was given to eight normal subjects and observed that in the hyperthyroid subject, plasma dipyrone levels were normal and the urinary excretion of 4-aminoantipyrine was decreased.…”
Section: Concentration-effect (#-Blockade) Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…In the dog, Vesell et al (1973) found a good inverse correlation between antipyrine T, and the activity of hepatic microsomal aniline hydroxylase and ethylmorphine N-demethylase whereas in man Davies, Thorgeirsson, Breckenridge & Orme (1973) were unable to demonstrate a correlation between antipyrine clearance and the rate of N-demethylation of the ethylmorphine in vitro. Furthermore, in vivo and in vitro studies in laboratory animals suggest that thyroid hormone may inhibit the N-demethylation of aminopyrine (Kato & Gillette, 1965;Kato, 1977). Brunk et al (1974) found no change in dipyrone metabolism when liothyronine was given to eight normal subjects and observed that in the hyperthyroid subject, plasma dipyrone levels were normal and the urinary excretion of 4-aminoantipyrine was decreased.…”
Section: Concentration-effect (#-Blockade) Relationshipmentioning
confidence: 99%
“…Thirdly, since the phenobarbitone treatment did not distort the elimination kinetics of propranolol, a drug interaction between barbiturate and propranolol seems unlikely. Finally, since the available data so far do not allow a general statement about drug disposition and since various pathways and substrates are apparently affected in different ways by thyroid dysfunction (Eichelbaum, 1976;Kato, 1977), each drug must be studied individually in thyroid disorders. Furthermore, the disposition data of certain drugs obtained from artificially-induced hyperthyroidism of an animal species as in this study may not be directly applicable to those in the spontaneously occurring human hyperthyroid state.…”
Section: Concentration-effect (#-Blockade) Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetic calculations taking into account body weight suggest, however, that the over-all metabolism of antipyrine is normal in anorexia nervosa. The effect of starvation and restricted feeding on drug metabolism is complex both in animals and in man (Kato, 1977). Significant sex differences exist in that the activity of some NADPH-dependant enzymes in the liver microsomes is depressed in male rats and stimulated in female rats after starvation.…”
Section: Antipyrine Metabolism In Anorexia Nervosamentioning
confidence: 99%
“…Nutritional and endocrine factors influence the disposition of many drugs which are metabolized by the liver (Eichelbaum, 1976;Kappas, Anderson, Conney & Alvares, 1976;Stevenson, 1977;Kato 1977). Grave malnutrition and hypometabolism associated with low concentrations of triiodothyronine and thyroxine in plasma and decreased metabolism of cortisol are prominent features of anorexia nervosa (Boyar, Hellmann, Roffward, Katz, Zumoff, O'Connor, Bradlow & Fukushuma, 1977).…”
Section: Antipyrine Metabolism In Anorexia Nervosamentioning
confidence: 99%